(untitled) (Communications in Computational Physics, 2013)
This study mainly focused on the key technologies, the photon dose calculation based on the Monte Carlo Finite-Size Pencil Beam (MCFSPB) model in the Accurate Radiotherapy System (ARTS). In the MCFSPB model, the acquisition of pencil beam kernel is one of the most important technologies. In this study, by analyzing the demerits of the clinical pencil beam dose calculation methods, a new pencil beam kernel model was developed based on the Monte Carlo (MC) simulation and the technology of medical accelerator energy spectrum reconstruction, which greatly improved the accuracy of calculated result. According to the axial symmetry principle, only part of simulation results were used for the data of pencil beam kernel, which greatly reduced the data quantity of the pencil beam and reduced calculated time. Based on the above studies, the MCFSPB method was designed and implemented by the Visual C++ development tool. With several tests including the comparisons among the American Association of Physicists in Medicine (AAPM) No. 55 Report sample and the ion chamber measurement of lung-simulating inhomogeneous phantom in clinical treatment plan, the results showed that the maximum error of most calculated point was less than 0.5% in the homogeneous phantom and less than 3% in the heterogeneous phantom. This method met the clinical criteria, and would be expected to be used as a fast and accurate dose engine for clinic TPS.